Can Hops (cones of Humulus lupulus L.) Cure What Ails You? Relating Hop Chemistry to Bioactivity - Pusiak, Ryan (Université d'Ottawa | University of Ottawa, 2024)
This thesis used biochemometrics, metabolomics, and bioassay-guided fractionation to quantify, group, and identify active chemical constituents in hop (Humulus lupulus L. Cannabaceae) extracts, a phytochemically unique plant of cultural and economic significance around the world. Hops produce infructescence (cones) from the female plant that contain < 30% (dry weight) secondary metabolites such as the polyketides humulones (α-acids), lupulones (ß-acids), and prenylated chalcones (e.g., xanthohumol), that were quantified via high-performance liquid chromatography with diode array detection (HPLC-DAD). Hops have anti-bacterial, anti-inflammatory, and sedative properties, though most are destined for the brewing industry. However, the traditional uses, unique metabolites, and reported bioactivity of hops have led to increasing interest in hops as a natural health product. Hop breeders select hops for their unique chemical properties (aroma or bittering) that differ between varieties. Previously, it was found that the alpha acids were positively correlated to xanthohumol, though the relationship between alpha acids and beta acids remained unclear. Alpha acids (co- and ad-humulone) correlated with one another, beta acids (lupulone, colupulone, and adlupulone) correlated with one another, and the individual alpha acids correlated more strongly with xanthohumol than the individual beta acids did with xanthohumol. Indigenous North American hops usually have greater alpha acid content than European hops. Bittering hops and North American hop samples contained significantly more alpha acids (humulone, cohumulone, and adhumulone). They had a higher alpha-to-beta ratio than the aroma and European hop samples. The biochemometric approach uses a chemically diverse set of plants and modelled bioactivity to chemistry from these HPLC data, along with testing isolated constituents of hops, metabolomic analysis on the hop extracts using ultra-performance liquid chromatography with high resonance mass spectroscopy, and bioassay-guided fractionation to identify other compounds or confirm the identity of targeted compounds. Free radicals are sometimes a natural byproduct of cellular respiration; enzymes typically scavenge these free radicals. However, oxidative stress occurs when free-radical production outpaces free-radical scavenging activity (RSA). Continued oxidative stress leads to an inflammatory response and activation of oxidase enzymes, such as cyclooxygenase-2 (COX-2). The endocannabinoid system consists of receptors, ligands, and enzymes that metabolize endocannabinoids (e.g., FAAH and MAGL). FAAH and MAGL inhibition increases endocannabinoids levels, reducing the quantity of arachidonic acid used by some inflammatory pathways (e.g., COX-2 and LOX). Hop extract chemistry modelled RSA and FAAH inhibitory activity based on marker compounds. In contrast, extract chemistry did not model COX-2 and MAGL inhibitions as there was a narrow activity range among extracts. Isolated n-adlupulone demonstrated the strongest RSA, comparable to ascorbic acid. Xanthohumol potently inhibited COX-2, FAAH, and MAGL. Colupulone potently inhibited COX-2 and MAGL. Mass features were tentatively identified from the metabolomics dataset and modelled bioactivity, while bioassay-guided fractionation confirmed xanthohumol as a strong FAAH and MAGL inhibitor. This is the first study to use biochemometrics, metabolomics, and bioassay-guided fractionation to identify bioactive components in hops and that assessed isolated compounds in a concentration-dependent manner. These results will further support the development of hop-based natural health products.
Keywords: Humulus lupulus; biochemometrics; endocannabinoid system; metabolomics; bioassay-guided fractionation